Virtual machine co-residency method on cloud computing platform - Weijie LIU; Li’na WANG; Danlei WANG; Zhengguang YIN; Nan FU (Tongxin xuebao)
If the attacker wants to compromise a target virtual machine on a cloud platform,the malicious virtual machine must be co-resident with the target.Based on this,a virtual machine co-residency method was proposed.The method combined a co-residency detection scheme based on covert channel construction and an automatic virtual machine flooding strategy,and was evaluated on a well-known domestic cloud platform.Experiment shows that the adaptive covert channel can achieve accuracies of 95%,the proposed detection scheme has strong robustness whose false positive rate is less than 5 ‰,the proposed method is versatile and keeps the virtualization isolation barrier intact,which has great potential threat and should be paid great attention and precaution.